PENGARUH BRAND DRIVERS TERHADAP PERILAKU PERPINDAHAN TEMPAT BERKUMPUL DI KOTA SEMARANG DENGAN KEPUTUSAN PEMILIHAN SEBAGAI VARIABEL INTERVENING (Studi Pada Mahasiswa Universitas Diponegoro Semarang) - Ugaje, Wahyu Ruland; Santoso, Suryono Budi (Faculty of Economics and Business Diponegoro University, 2017)
The problem of this research begins when in big cities a lot of popping place cafe that is built according to the tastes and needs of young people. In the city of Semarang, the number of cafes suitable for hangout spread throughout the city, one of which is phenomenal Han's Coffee. Coffee Coffee Han on Kusumawardani Street, Pleburan Village. Facilities and menu Han's Coffee Semarang quite diverse, ranging from drinks, snacks and have a concept free of drugs and liquor, so no wonder Han's Coffee Semarang crowded from morning to night, let alone Han's Coffee Semarang open for 24 hours.The purpose of this study is to determine the effect of product, service quality, facilities and price on the displacement behavior. The method of this research is quantitative with the data instrument that got the questionnaire distributed to 100 respondents by using proportional random sampling technique, because the researcher divide the date on Tuesday (quiet) and crowded (Saturday) according to the proportion.The results of this study used multiple linear regression formula with the help of SPSS; product, service quality and facilities partially or simultaneously. Furthermore, the variables of facilities, prices and purchasing decisions partially to the movement of the gathering place. Product variables and quality of partial service are not migratory to the shifting place of assembly. Simultaneously the product variables, service quality, facilities, price and purchase decisions affect the movement of the gathering place.The end result (X1), quality (X2), price (X3), price (X4) and purchasing decision (Y1) orientation to the shifting place (Y2). As the magnitude of influence is 0.265 or 26.5 percent, meaning 100% -26.5% = 73.5% are independent variables of independent variables outside product variables (X1), service quality (X2), facility (X3) , price (X4) and purchase decision (Y1). From variable free variable see facility variable (X3) is the most dominant variable influence the movement of camping place, that is equal to 30,7 percent.